Kepemimpinan Visioner Terhadap Pembangunan Berkelanjutan di Kota Baubau - A, Herry Pratama; Gazalin, Junaid; Sarsina, Wa Ode; Oksahill, Oksahill; Eriman, Laode (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to analyze the role of visionary leadership in supporting sustainable development in Baubau City, particularly in the context of the development of the Kota Mara (Kotamara) area. Visionary leadership is identified as a key factor in formulating strategic policies oriented towards sustainability, including economic, social, and environmental aspects. This study used a qualitative approach with a descriptive-analytical method, through in-depth interviews, observation, and document review. The results show that visionary leadership is able to create synergy between the government, community, and private sector in realizing sustainable development. Leaders with a long-term vision play a role in designing innovative programs, such as community participation-based environmental management, environmentally friendly infrastructure development, and strengthening the local economy. In addition, visionary leadership is also a catalyst in building collective awareness of the importance of sustainability as the main foundation of development. This study concludes that the consistent implementation of visionary leadership can be an effective model to encourage city transformation towards inclusive and sustainable development.